If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x(2x + 7) = -24 Reorder the terms: 8x(7 + 2x) = -24 (7 * 8x + 2x * 8x) = -24 (56x + 16x2) = -24 Solving 56x + 16x2 = -24 Solving for variable 'x'. Reorder the terms: 24 + 56x + 16x2 = -24 + 24 Combine like terms: -24 + 24 = 0 24 + 56x + 16x2 = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(3 + 7x + 2x2) = 0 Factor a trinomial. 8((3 + x)(1 + 2x)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {-3, -0.5}
| -9c-3+8c=22 | | X^2+14=-86 | | 9n+4a-6n-2a= | | 25=-5w | | e=2d+4p | | 9/-3+m=10 | | 19z-4+12z=16z-1+141/3z | | 5x=-13x+7 | | 2b+3a-a+5b= | | 6x-(2x+3)=25 | | 17x^2-4x=0 | | 5.9p-4.2-4.9p=-6.2 | | 2(5m-6)-15=-9 | | sqrt(x+1)+sqrt(x+2)=3 | | 3(x+1)+1=2(x-1)+3 | | 9x+2=7x-10 | | 6x-4-4x-3= | | 19=4(w-2)+5w | | 2(x-5)+20=40 | | 6z-14=-18 | | x=0.6410256410y | | 2(5m-6)-12-15=-9 | | 17=-5v+8(v+4) | | 5/57.25 | | 7x(4x+2)=5 | | 2x+3(3x+17)=183 | | 3+6+x=5+4 | | 5v+3v-18=-74 | | 2x-5=3+2 | | 8p+4=-21 | | 10(x-1)+(4x+14)+22=82 | | 3x-2/4=-3 |